2020
DOI: 10.5194/acp-2020-768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward closure between predicted and observed particle viscosity over a wide range temperature and relative humidity

Abstract: Abstract. Atmospheric aerosols can exist in amorphous semi-solid or glassy phase states whose viscosity varies with atmospheric temperature and relative humidity. The temperature and humidity dependence of viscosity has been hypothesized to be predictable from the combination of a water-organic binary mixing rule of the glass transition temperature, a glass transition temperature scaled viscosity fragility parameterization, and a water uptake parameterization. This work presents a closure study between predict… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…D f , which characterizes the deviation of the temperature dependence of viscosity from an Arrhenius behavior, , was assumed to be 10 based on our previous study . The value of D f is assumed to be independent of RH. ,,, This assumption is consistent with previous studies that found that the value of D f in sucrose and citric acid is independent of water content, except for anhydrous sucrose. ,, …”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…D f , which characterizes the deviation of the temperature dependence of viscosity from an Arrhenius behavior, , was assumed to be 10 based on our previous study . The value of D f is assumed to be independent of RH. ,,, This assumption is consistent with previous studies that found that the value of D f in sucrose and citric acid is independent of water content, except for anhydrous sucrose. ,, …”
Section: Methodsmentioning
confidence: 67%
“…54,55,101,102 This assumption is consistent with previous studies that found that the value of D f in sucrose and citric acid is independent of water content, except for anhydrous sucrose. 99,103,104 2.5. Prediction of Viscosity Using a Mole-Fraction Based Arrhenius Mixing Rule.…”
Section: Methodsmentioning
confidence: 99%
“…30 However, these techniques are limited to large particles or aerosol material masses and could not be extended to the sub-micron size range. Viscosity and phase state of nanoparticles has been assessed based on dimer coalescence, [31][32][33][34][35] but this technique is limited by narrow accessible viscosity range (10 5 -10 8 Pa s). Moreover, these techniques mentioned above are mainly designed based on surrogates of ambient particles, making it a challenge to apply them in the direct measurements of ambient aerosol particles viscosity.…”
Section: Introductionmentioning
confidence: 99%